Youth Interest in Korean Culture (K-Pop) and its Impact on Indonesian Nationalism - Wasilatul Aslamiyah; Edy Herianto; Bagdawansyah Alqodri (Universitas Mataram, 2023)
Korean culture, becoming popular in Indonesia, has impacted its lovers. In addition, the media also plays a role in causing the emergence of Korean fever in society. Korean culture and style have become popular culture, not only about music; many people also like dramas or films related to Korean culture. This development began to affect the public, especially Civics Education students at the University of Mataram. This research was conducted to explain the impact of Korean culture on the level of nationalism of youth interested in Korean culture. The results illustrate that young people are willing to spend special funds to adopt Korean cultural styles by following fashion and collecting items related to their idols from Korea. Even so, youth admit that nationalizing Indonesia remains the first choice. Being interested in Korean culture is part of the fun. It did not affect his love for Indonesian nationalism.